Influence of banded ε-martensite and deformation twin on cryogenic toughness of Fe–Mn–xAl–C steel - Li, Leilei (2024)
Fe–Mn–xAl–C steel ingots have been fabricated by vacuum melting with Al compositions varied from x = 0 to 3 and 5 wt.%, respectively. After properly hot-forging and hot-rolling as well as solution heat treatments, impact toughness tests were carried out at 77 K using a standard full-size of Charpy impact V-notch configuration. It was found that the addition of Al element is more conducive to enhance the cryogenic toughness. The relationship between the cryogenic toughness and the Al composition has been revealed through detailed microstructural studies by electron back scatter diffraction and transmission-electron microscopy. The stack fault energy (SFE) increases with the increase of Al content at various temperature. The plastic deformation is dominated by deformation bands which are dominated by deformation twins (DTs) and ε-martensite at x = 0 and DTs at x = 3 and 5%, respectively. The DTs near fracture the notch-tip area increased in the order of the 0Al, 3Al, and 5Al steel. The DTs with high density, together with their contented dislocations, significantly contributed to the high cryogenic toughness of the studied high manganese steel with higher Al content. Banded ε-martensite will deterioration cryogenic toughness due to its large size compared to DTs at 0Al steel.